Iowa Birdline update, October 25, 1994 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1994)
Iowa Birdline update for October 25, 1994 . Highlights of the update include details on the continuation of the fall migration with Hawks and shorebirds on the move, including sightings of a Peregrine Falcon, an immature Cooper's Hawk, Long-billed Dowitchers, and White-rumped Sandpipers. Other observations of note include a late Philadelphia Vireo, a late Yellow-rumped Warbler, and a first winter Laughing Gull. Epson - sheet feed/flatbed